What are karrikins and how were they 'discovered' by plants? - Flematti, G.; Dixon, Kingsley; Smith, S. (BioMed Central Ltd., 2015)
© 2015 Flematti et al. Karrikins are a family of compounds produced by wildfires that can stimulate the germination of dormant seeds of plants from numerous families. Seed plants could have 'discovered' karrikins during fire-prone times in the Cretaceous period when flowering plants were evolving rapidly. Recent research suggests that karrikins mimic an unidentified endogenous compound that has roles in seed germination and early plant development. The endogenous signalling compound is presumably not only similar to karrikins, but also to the related strigolactone hormones.